Semiotic analysis of ramo-ramo tabang duo dance and its character education implications - Mairita Mairita; Jupriani Jupriani; Indrayuda Indrayuda; Syilendra Syilendra (Global Econedu, 2026)
This study aims to analyze the semiotic meanings of Ramo-Ramo Tabang Duo Dance and examine their implications for student character education. This research employed a qualitative interpretative case study using Charles Sanders Peirce’s trichotomy of signs: icon, index, and symbol. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the dance movements, costumes, and floor patterns contain symbolic meanings representing religiosity, harmony, discipline, cooperation, responsibility, integrity, and cultural awareness. These values are aligned with Indonesia’s Character Education Strengthening Program. Ramo-Ramo Tabang Duo Dance can serve as a contextual medium for preserving local cultural heritage while strengthening student character through culturally responsive education.